The feasibility of a “no tube, no fasting” fast-track recovery protocol after esophagectomy for esophageal cancer patients aged 75 and over - Xing, Wenqun; Liu, Xianben; Miao, Peng; Hao, Wentao; Li, Keting; Wang, Hao; Zheng, Yan (Frontiers in Oncology, 2023)
Objective For elderly patients aged ≥75 with esophageal cancer, whether surgical treatment is safe and effective and whether it is feasible to use a relatively radical “no tube, no fasting” fast-track recovery protocol remain topics of debate. We conducted a retrospective analysis to shed light on these two questions. Methods We retrospectively collected the data of patients who underwent McKeown minimally invasive esophagectomy (MIE) combined with early oral feeding (EOF) on postoperative day 1 between April 2015 and December 2017 at Medical Group 1, Ward 1, Department of Thoracic Surgery of our hospital. Preoperative characteristics, postoperative complications, operation time, intraoperative blood loss, duration of anastomotic leakage (day), hospital stay, and survival were evaluated. Results Twenty-three elderly patients with esophageal cancer underwent surgery with EOF. No significant difference was observed in intraoperative measures. The incidence of postoperative complications was 34.8% (8/23). Two patients (8.7%) were terminated early during the analysis of the feasibility of EOF. For all 23 patients, the mean hospital stay was 11.4 (5-42) days, and the median survival was 51 months. Conclusion Patients aged ≥75 with resectable esophageal cancer can achieve long-term survival with active surgical treatment. Moreover, the “no tube, no fasting” fast-track recovery protocol is safe and feasible for elderly patients.